Spark plasma sintering of boron carbide composite for defence application - Tit, Jie En (2015)
Boron Carbide has been a popular research topic in defence science. Besides possessing excellent mechanical properties such as high hardness, low density, high melting point, it also possesses excellent chemical stability. However, it possesses two key issues when used as a defence material: its relatively low fracture and its susceptibility to thermal shocks (especially during production). These issues have traditionally prevented large-scale production of boron carbide. The brittleness of boron carbide is due to numerous intrinsic factors, such as the strong covalent bonding of B-C and the material’s low surface diffusivity. To resolve these problems, various innovative methods have been devised. One of the breakthroughs is to utilise the novel method of Spark Plasma Sintering (SPS), to sinter boron carbide. Through the innovative technique, densities of up to 99% of boron carbide’s theoretical value can be achieved within a very short period of time. Due to these desirable advantages, the SPS technique had become one of the key methods to produce boron carbide for defence applications. In this project, twin-layered boron carbide was sintered at 1850ºC at various heating rates by SPS. The influence of heating rate on the densification process, microstructure and physical property was investigated. An increase in the heating rate was found to generally increase the hardness of the boron carbide, but decrease its fracture toughness and porosity. However, the relationship between heating rate and density was not established. The optimum heating rate was 38.3 ºC per minute when heated from 700 ºC to 1850 ºC. The relative density, Vickers hardness, fracture toughness and porosity. The initial grain-size of the powder used seems to be a key factor to create fine-grained and fully-dense samples. The mechanism for densification during SPS is also discussed.